Biochemical Effects of Some Peroxisome Proliferator Activated Receptor Ligands in Hyperhomocysteinemic-rats - Ghada M. Al-Ashmawy, Hoda A. El-Bahrawy, Nahla E. El-Ashmawy (Journal of Applied Pharmaceutical Science, 2013)
Hyperhomocysteinemia (HHcy) is implicated in peripheral vascular, cerebrovascular and coronary heart disease. This study was conducted to investigate the effects of pioglitazone (PPAR-γ agonist) and gemfibrozil (PPAR-α agonist), either alone or in combination, in HHcy-rats. HHcy was induced by keeping rats on high methionine diet (8% w/w) for 6 weeks. Rats were divided into two major groups; normal fed rats and methionine overload rats. Each group was further subdivided into four subgroups: a) control group, b) pioglitazone (10 mg/kg), c) gemfibrozil (100 mg/kg), and d) combination of the chosen PPAR ligands. The drugs were given orally daily for consecutive six weeks. The results showed that the great reduction of HHcy was obtained by the drug combination. Induction of HHcy in rats resulted in elevation of LDL-cholesterol and suppression of HDL-cholesterol. Hepatic paraoxonase-1 activity was inhibited in all HHcy-rat groups. RT-PCR for liver cyclooxygenase-2 (COX-2) showed marked expression in HHcy-rats, which was attenuated by treatment with PPAR agonists. RT-PCR for cystathionine β-synthase (CBS) showed positive expression in all HHcy-rat groups except that treated with combination of PPAR ligands. These results suggest that pioglitazone-gemfibrozil combination showed ameliorative effect on hyperhomocysteinemia and its consequences in rats.
Keywords: Hyperhomocysteinemia, Pioglitazone, Gemfibrozil, Nit